Data on the Ecological Composition and Functional Distribution of Insect Communities in Onshore Wind Farms - Jin Lee; Sung-soo Kim; Do-hun Lee (Geo Data)
This study was conducted to identify changes in insect composition and function before and after the construction of onshore wind farms. We investigated insect fauna, composition, and functional groups in grassland and forest sites at the operational Muchang Wind Farm (MC) in Yeongdeok and Yeongyang, Gyeongsangbuk-do, and the planned Gasan Wind Farm (GS) in Jeongsun, Gangwon-do, Korea. Insects were collected using a sweeping net, pitfall traps, and light traps. A total of 12 orders, 75 families, and 2,497 individuals were collected across the study sites. Among taxonomic groups, the order with the highest species and individual counts was Lepidoptera, with 222 species and 628 individuals (25.0%), followed by Coleoptera, with 81 species and 241 individuals (23.5%). Additionally, based on functional groups such as herbivores, predators, decomposers, etc., the results reveal distinct differences in the proportion of these groups between grasslands created by habitat disturbance at the operational MC site and those at the planned GS site. The findings of this study provide valuable insights into the effects of habitat changes due to onshore wind farm establishment on insect communities.